The allocation of seats in the European Parliament and the principle of degressive proportionality - Peternek, Piotr; Kośny, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
One of the key issues in the process of preparing for an election to the European Parliament is to determine the number of seats for each country. The Treaty of Lisbon, signed by Member States of the European Union, has obliged the European Parliament to establish rules guaranteeing that the distribution of seats should be done according to, inter alia, the principle of degressive proportionality. The purpose of this paper is to explore how the principle of degressive proportionality is actually implemented, and to propose a compromise – a mathematical solution, guaranteeing that the distribution of seats is consistent with the requirements of the Lisbon Treaty.
Mathematical Economics, 2015, Nr 11 (18), s. 99-113
Keywords: European Parliament; degressive proportionality; optimization